Deaf Languages: Does the Hypothesis Still Apply? - Laurence Vincent-Durroux (Corela)
In the 1990s, studies on the syntax and semantics of oral profoundly deaf children and teenagers established the existence of Deaf Languages in subjects with aided thresholds outside the range of conversation levels. Presently, cochlear implants and hearing aids may yield good auditory benefit. It is therefore necessary to evaluate if the hypothesis of Deaf Languages still applies in these conditions. The syntactic and semantic features of oral data gathered from 6 French and 6 English children and teenagers with at least 7 years of implant use were therefore analyzed and compared to a similar set of data gathered in 1988, from 4 French-speaking and 4 English-speaking oral profoundly deaf children and teenagers. Remaining patterns of Deaf Languages are still to be found and linguistic aspects such as meta-linguistic comments, metaphoric use, humor, and complex sentences emerge. The lack of aural perception in the early months could be responsible for the development of specific cognitive representations, especially of time and space, which may account for persistent patterns of Deaf English despite the subsequent greater amount and variety in linguistic input.